Clinicopathologic features of ovarian neoplasms with emphasis on borderline ovarian tumors: an institutional perspective. (December 2016) - Hashmi, Atif; Hussain, Zubaida; Bhagwani, Aneel; Edhi, Muhammad; Faridi, Naveen; Hussain, Syed; Khan, Mehmood
Abstract Background Ovarian cancer is the most lethal gynecologic malignancy and it represents third most common malignancy in Karachi (after breast and oral cancer). Due to lack of well established cancer registry in our country, changing trends of ovarian tumors has not been determined. Therefore we aimed to establish the current trends and classification of ovarian tumors in our setup according to latest WHO guidelines. Methods We retrospectively analyzed 162 cases of ovarian tumors that underwent surgical resection from January 2009 till December 2014. Specimens were received in histopathology department, Liaquat National hospital and cases were examined by senior histopathologists and classified according to latest WHO guidelines. Various histopathologic parameters including capsular invasion, omental and lymph node meatstasis along with uterine and fallopian tube involvement were determined apart from tumor type and grade. Results Mean age at diagnosis was 35.8 years (± 15.5). surface epithelial tumors were most common, 109 cases (67.2 %) followed by germ cell tumors, 44 cases (27.1 %) and sex cord stromal tumors, 8 cases (4.9 %). Serous tumors were most common surface epithelial tumors with 90 % benign morphology. On the other hand, mucinous tumors showed a higher percentage of borderline and malignant features (16.7 and 14.6 % respectively). Higher incidence of capsular invasion and omental metastasis was noted in endometroid and serous carcinoma compared to mucinous tumors. Conclusions We noted a higher frequency of young age ovarian cancers in our set up. Serous and endometroid carcinomas were found to be associated with adverse prognostic factors like capsular invasion and omental metastasis. Moreover a significantly higher proportion of ovarian tumors constitute mucinous histology including borderline tumors. Whether this represents a changing trend towards biology of these tumors in this part of the world needs to be uncovered by further studies.